Pendampingan Digital Marketing Pada UMKM Bakso Dan Es Campur “Family” Sebagai Penunjang Kegiatan Promosi Dan Pemasaran - Ainurriyah Ainurriyah; Sugeng Purwanto (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
Micro, Small and Medium Enterprises (MSMEs) have a very important role in the Indonesian economy. In the era of technological development and digitization in various fields, MSMEs as a type of business that has a large role in building the economy also need to experience development in the field of technology in marketing their products. The purpose of this service is to develop MSMEs in terms of digital marketing and expand the MSMEs marketing network. One example of MSMEs that need digital marketing assistance is UMKM Meatballs and Mixed Ice "Family". The method used in this community service activity is divided into four stages, namely the survey stage, the digital marketing socialization stage, digital marketing assistance and the maintenance and evaluation stages. Digital marketing assistance activities for UMKM Meatballs and Mixed Ice "Family" are a form of community service with the aim of developing and participating in elevating regional potential so that they can have a marketing network that is not limited to the local market.